2011
DOI: 10.1007/s00415-010-5883-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural gray and white matter changes in patients with HIV

Abstract: In this cross-sectional study we used magnetic resonance imaging (MRI)-based voxel based morphometry (VBM) in a sample of HIV positive patients to detect structural gray and white matter changes. Forty-eight HIV positive subjects with (n = 28) or without (n = 20) cognitive deficits (mean age 48.5 ± 9.6 years) and 48 age- and sex-matched HIV negative controls underwent MRI for VBM analyses. Clinical testing in HIV patients included the HIV dementia scale (HDS), Unified Parkinson's Disease Rating Scale (UPDRS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
106
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 42 publications
23
106
1
2
Order By: Relevance
“…[9][10][11][12][13] Previous studies also found smaller volumes in several specific anatomical structures, such as the basal ganglia, 9 caudate, 11,13,14 putamen, 14 and total cortex volume of HIV-positive patients. 12 These studies found a correlation between diffuse brain atrophy and motor impairments, 10,14 dementia severity 10 and CDC stages of HIV infection, 11,13 smaller basal ganglia volume and motor dysfunction, 15 caudate and putamen atrophy and longer disease duration. 14 Similarly to these studies, we observed smaller volumes predominantly in the basal ganglia, primarily in the caudate, in HIV-positive patients with cognitive deficits.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[9][10][11][12][13] Previous studies also found smaller volumes in several specific anatomical structures, such as the basal ganglia, 9 caudate, 11,13,14 putamen, 14 and total cortex volume of HIV-positive patients. 12 These studies found a correlation between diffuse brain atrophy and motor impairments, 10,14 dementia severity 10 and CDC stages of HIV infection, 11,13 smaller basal ganglia volume and motor dysfunction, 15 caudate and putamen atrophy and longer disease duration. 14 Similarly to these studies, we observed smaller volumes predominantly in the basal ganglia, primarily in the caudate, in HIV-positive patients with cognitive deficits.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have assessed the cortical thickness of HIVpositive patients and showed atrophy in anterior cingulate and temporal cortices, 15 primary sensory and motor cortices, parietal association cortex, medial frontal and premotor cortex, 16 posterior and inferior temporal lobes, parietal lobes, and in the cerebellum. 18 A study found a reduction in cortical thickness in the bilateral insula, orbitofrontal and temporal cortices and right superior frontal cortex in patients using HAART, with detectable HIV-deoxyribonucleic acid (DNA) in peripheral blood, compared with HIV patients using HAART without HIV-DNA detected in peripheral blood, which was correlated with psychomotor speed dysfunction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study with 94% of participants treated with ART, impaired motor function was associated with basal ganglia gray matter atrophy. 55 A study with 100% ART-treated subjects demonstrated a correlation between cortical thinning and reduced psychomotor speed. 56 Another study of 100% ART-treated subjects revealed correlations between decreased TBv and reduced motor function and processing speed, and decreased thalamic volumes with reduced motor function.…”
mentioning
confidence: 99%
“…Some authors reported volumetric changes in the cortical areas, basal ganglia and white matter in HIV-infected patients at different stages of their disease: these changes were more severe in most advanced stages but were evident even in asymptomatic individuals [46]. Other authors reported a severe gray matter reduction in the left lateral temporal and anterior cingulate cortex in HIV patients with cognitive impairment (even if the decline was mild), and a white matter atrophy in the frontal lobe and within the midbrain [47]. In the same study, there was no difference between HIV-negative controls and HIV patients with normal cognitive performance [47].…”
Section: Discussionmentioning
confidence: 94%